First interim report on fluid diodes - Taylor, A. F. (College of Aeronautics, 1969)
A description of the various forms of fluid diode and report of tests done on a breadboard unit leading to the manufacture and testing of a prototype 1 14u vortex diode. This work was carried out under contract for Flight Refuelling Ltd. (ref. order no.D.15795 of 2.5.69) and is the first of a series to cover a preliminary study of fluidic and allied devices in aircraft low pressure fuel systems.